The Impact of Ifan's Leadership in Seventeen and Fan Support on the Continuation of Seventeen's Music Career Following the Tsunami Tragedy - Safa Ricci Amanda (Jurnal Indonesia Sosial Sains, 2026)
This study aims to analyze the influence of Ifan Seventeen's leadership and fan support on the sustainability of the Seventeen Band's music business after the 2018 tragedy. The method used was quantitative with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, involving 109 respondents obtained through the distribution of an online questionnaire. The independent variables in this study were leadership (X1) and fan support (X2), while the sustainability of the Seventeen Band's music business became a dependent variable (Y). The results of the study show that Iwan's leadership and fan support have a significant effect on the sustainability of the music business, both partially and simultaneously. An R-square value of 0.974 indicates that both independent variables are able to explain 97.4% variation in band sustainability. These findings affirm the importance of symbolic leadership and emotional engagement of fans in maintaining the existence of music brands in the midst of a crisis, as well as contributing to the development of artist management strategies and strengthening audience loyalty in the Indonesian music industry.